SISTEM BUNGA DALAM BISNIS MODEREN (SUATU ANALISIS BERDASARKAN HUKUM ISLAM) - Hilal Mallarangan (Hunafa: Jurnal Studia Islamika, 2007)
The urgency of business cannot be neglected. Business always performs a vital role in a social life and of economy of mankind. Nonetheless, in Islamic perspective, a business is not for a mere business. In other words, a business must be managed under the system of rahmatun lil ‘alamin (blessing for all mankind). This article deals with one of the important pillars in modern business, that is interest system, especially   bank interest system, which will be analyzed based on the Islamic law. After analyzing the subject using the Qur’an and the prophet’s traditions as well as Islamic legal maxims, the writer finds a variety of arguments put forward by the Islamic law experts in drawing a conclusion on the permission and  the banning of bank interest. Apart from this controversy, in the writer’s point of view, fund and the empowerment of umat economy must be institutionally supported.Kata Kunci:   sistem bunga bank, riba, business modern, hukum Islam